Keteladanan Guru Pendidikan Agama Kristen Dalam Meningkatkan Nilai-Nilai Tata Krama Peserta Didik SD Negeri 07 Pinang Sebatang Barat - Simbolon, Mustika (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2022)
A teacher is not only a resource person in knowing and mastering the subject matter but also being a role model for students. Being a teacher is not an easy thing, apart from being able to teach and educate, it is also a role model in good actions and deeds. The Importance of Exemplary Christian Religious Education Teachers can increase the moral values ​​of students. PAK teachers are teachers, educators and role models, both in words, actions, faith and love. The purpose of this study is to explain how the general description of the example of PAK teachers. Then explain how the example of PAK teachers in increasing the values ​​of student manners. The research method used in collecting and compiling this thesis is a qualitative research literature (library research). The author describes each view or theory of the experts and arranges them sequentially. The results obtained in this study are exemplary providing good examples to students and being responsible for the tasks that have been given to them. The success of a PAK teacher is to start with him first. It can happen through talent, personality, preparation and right relationship with God. PAK teachers must have good and polite behavior in their lives, both in the school environment and in the community. The example of Christian Religious Education Teachers will improve the students' karma